Analisis Sistem Dan Teknologi Informasi Sebagai Acauan Dalam Perancangan Rencana Strategis Sistem Informasi Dan Teknologi Informasi (Renstra Si/Ti) Di Rumah Sakit Islam Yogyakarta Pdhi - Fahmi Hakam (Jurnal Sistem Informasi, 2017)
In general the use of IS / IT within the Islamic Hospital in Yogyakarta PDHI less than optimal and not show the direction of good information systems development. Then not supported by the management system and work processes that are effective, and there is no strategic plan for the development of the IS / IT. This study aimed to analyze the information systems and information technology, which can be used to base the development of the strategic plan of IS / IT in Islamic Hospital Yogyakarta PDHI. This study is case study, using a qualitative approach. Collecting data in this study using interviews, FGD to management and observation, as well as the review of the document. This study tries to identify the conditions and needs of organizations in planning strategies IS / IT RSIY PDHI. Islamic Hospital Yogyakarta PDHI already implementing HIS, but the existing information systems is not supported by legal documents used as a referral organization in the development of the IS / IT, other than that related to the architecture of IS / IT and the development of HIS is already done, shows that RSIY PDHI not conform with existing standards and protocols. There is still a gap between the conditions of IS / IT in RSIY PDHI standards of governance and architecture / IT, as well as management standards HIS.